Vascular injury of immature epiphyses impair stem cell engraftment in cartilage defects - Ali Rashidi; Ashok J. Theruvath; Ching-Hsin Huang; Wei Wu; Elhussein E. Mahmoud; Joe Gerald Jesu Raj; Krzysztof Marycz; Heike E. Daldrup-Link (Scientific Reports, 2022)
Abstract The purpose of our study was to investigate if vascular injury in immature epiphyses affects cartilage repair outcomes of matrix-associated stem cell implants (MASI). Porcine bone marrow mesenchymal stromal stem cells (BMSCs) suspended in a fibrin glue scaffold were implanted into 24 full-thickness cartilage defects (5 mm ø) of the bilateral distal femur of six Göttingen minipigs (n = 12 defects in 6 knee joints of 3 immature pigs; age 3.5–4 months; n = 12 defects in 6 knee joints of 3 mature control pigs; age, 21–28 months). All pigs underwent magnetic resonance imaging (MRI) at 2, 4, 12 (n = 24 defects), and 24 weeks (n = 12 defects). After the last imaging study, pigs were sacrificed, joints explanted and evaluated with VEGF, H&E, van Gieson, Mallory, and Safranin O stains. Results of mature and immature cartilage groups were compared using the Wilcoxon signed-rank test. Quantitative scores for subchondral edema at 2 weeks were correlated with quantitative scores for cartilage repair (MOCART score and ICRS score) at 12 weeks as well as Pineda scores at end of the study, using linear regression analysis. On serial MRIs, mature joints demonstrated progressive healing of cartilage defects while immature joints demonstrated incomplete healing and damage of the subchondral bone. The MOCART score at 12 weeks was significantly higher for mature joints (79.583 ± 7.216) compared to immature joints (30.416 ± 10.543, p = 0.002). Immature cartilage demonstrated abundant microvessels while mature cartilage did not contain microvessels. Accordingly, cartilage defects in immature joints showed a significantly higher number of disrupted microvessels, subchondral edema, and angiogenesis compared to mature cartilage. Quantitative scores for subchondral edema at 2 weeks were negatively correlated with MOCART scores (r =  − 0.861) and ICRS scores (r =  − 0.901) at 12 weeks and positively correlated with Pineda scores at the end of the study (r = 0.782). Injury of epiphyseal blood vessels in immature joints leads to subchondral bone defects and limits cartilage repair after MASI.